PENERAPAN BRANCH AND BOUND ALGORITHM DALAM OPTIMALISASI PRODUKSI ROTI - SURYAWAN, GEDE; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (E-Jurnal Matematika; Vol 5 No 4 (2016), 2016)
Companies which engaged in production activities such as Ramadhan Bakery would want optimal profit in their every production. The aim of this study was to find optimal profit and optimal combination of bread production (original chocolate bread, extra chocolate bread, rounding chocolate bread and mattress chocolate bread) that was produced by Ramadhan Bakery by applying Branch and Bound Algorithm method. Branch and Bound Algorithm is one method to solve Integer Programming’s problems other than Cutting Plane method. Compared with Cutting Plane method, Branch and Bound Algorithm method is more effective in determining the optimal value. As the result of this study showed that to get optimal profit, Ramadhan Bakery should produce 360 pcs of original chocolate bread, 300 pcs of extra chocolate bread, 306 pcs of rounding chocolate bread and 129 pcs of mattress chocolate bread with optimal profit amounts Rp. 1.195.624,00.. The profit will increase amounts 25,2 % than before.
Keywords: Branch and Bound Algorithm; Optimal Profit; Optimize